THE GEOPOLITICAL CONTEXT IN THE THOUGHT OF FRANCISCO MORAZÁN - Molina, Silvia Elena (2018)
The purpose of this essay is to contextualize the ideas of Francisco Morazán about the process of conformation of the states in Central America after the Independence. In this work, the discourses pronounced by Morazán are taken as a base in order to distinguish the ideas, the relationships and the contradictions that were built inside the states, between the states, as well as in the relationships that they established with the powers during the first decades of the nineteenth century. This paper explores the evolution of the Federal Republic of Central America in a complex geopolitical context, and the ideas of Morazán around the conditions of possibility and expectations around this political project.